2022
DOI: 10.1021/acs.macromol.2c00459
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Li-Ion Transport in a Single-Ion Conducting Polymer Blend Electrolyte

Abstract: Single-ion conducting polymers (SICs) are promising candidates for the next generation of safer polymer electrolytes due to their stability and high transference number. However, the conductivity in SICs is often limited by the mobility of the polymer backbone as the ion mobility is coupled to segmental relaxations. We present polymer blend electrolytes, consisting of a precise s i n g l e L i -i o n c o n d u c t i n g p o l y m e r w i t h a (trifluoromethanesulfonyl)imide anion pendant group and a low molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…The inherent trade-off between high ion dissociation and rapid segmental dynamics makes it difficult to improve the ionic conductivity of polymer electrolytes. In other contexts, blending high-polarity and low-viscosity polymers has been studied as a strategy to overcome the transport limitations that arise in single-component polymer hosts. , Motivated by such studies, we examined the miscibility of 50:50 wt % PAGE/PCEGE blends as a function of LiTFSI concentration. Over the entire range of LiTFSI concentration investigated (0 < r < 0.2), two distinct T g s were observed as shown in Figure a, suggesting the coexistence of two phases.…”
Section: Resultsmentioning
confidence: 99%
“…The inherent trade-off between high ion dissociation and rapid segmental dynamics makes it difficult to improve the ionic conductivity of polymer electrolytes. In other contexts, blending high-polarity and low-viscosity polymers has been studied as a strategy to overcome the transport limitations that arise in single-component polymer hosts. , Motivated by such studies, we examined the miscibility of 50:50 wt % PAGE/PCEGE blends as a function of LiTFSI concentration. Over the entire range of LiTFSI concentration investigated (0 < r < 0.2), two distinct T g s were observed as shown in Figure a, suggesting the coexistence of two phases.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of design principles for SICs, percolated ionic aggregates offer a greater disparity in the mobility of counterions and polymer chains than discrete clusters. Our work highlights that adjusting the polarizability of pendant anion groups may dramatically increase the absolute value of the counterion diffusion constant for discrete aggregate morphologies, rationalizing the use of bulky or ionic liquid-type anions with delocalized charge as pendants . Although the counterion diffusion constant for discrete clusters is lower than that for percolated cluster systems, the drop-off is not as dramatic in the polarizable model as that in the non-polarizable model, which may extend the parameter space for design of ionomer materials used in energy applications.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the aggregates can also be influenced by the addition of plasticizing molecules or polymers that retain the shape of the aggregate while enabling faster fluidlike transport. For instance Paren et al 169 recently reported on styrene-based lithium single-ion conductors that strongly aggregate. Although the aggregates in this system are expected to structurally percolate, the transport through the ion channels in the absence of plasticizer is slow due to strong ion-polymer interactions and collapsed ion channels; however, the addition of plasticizing, low molecular weight PEO broadens the ion channels and allows for greater ion dissociation.…”
Section: Leveraging Alternative Ion Conduction Mechanismsmentioning
confidence: 99%